Communication Dynamics on WhatsApp Business and Their Impact on Patient Purchase Intention: An SEM–PLS Study (Case study from Edelweiss Hospital Bandung – Indonesia) - Iman Sulaeman (Asian Journal of Management Analytics, 2026)
This study investigates how three communication stimuli on WhatsApp Business visibility, interactivity, and authenticity affect purchase intention toward Edelweiss Hospital, with perceived value and perceived trust as mediating variables. A quantitative survey was conducted with 480 respondents who had interacted with Edelweiss Hospital through WhatsApp Business. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM–PLS). The results show that interactivity is the strongest predictor of perceived value, while authenticity is the main driver of perceived trust. Visibility shows a dual pattern: it increases perceived value but reduces trust and, through trust, weakens purchase intention. Perceived trust emerges as the strongest determinant of purchase intention, followed by perceived value. The findings extend the Stimulus Organism Response (S–O–R) framework into the digital healthcare context and offer practical guidance for hospitals on how to design and manage WhatsApp Business communication that truly supports patient decision-making.